LEADERS OF THE MUSLIM MOVEMENT RUSSIAN EMPIRE ABOUT KEY POLITICAL ISSUES THE BEGINNING OF THE XX CENTURY - Habutdinov, Ajdar Ur'evic; Imaseva, Marina Maratovna (History, Archeology and Ethnography of the Caucasus, 2020)
In the article, based on a wide range of documents, an attempt is made to analyze the interaction of the leaders of the Russian Muslim social movement on the main political issues of two key regions: the Volga-Ural and the Caucasus, at the beginning of the 20th century. We are talking about the cooperation of the leaders of the Muslim movement in considering the issues of the models of statehood and autonomy and land. The interaction of Muslims of the Volga-Ural region and the Caucasus in the framework of the activities of the Ittifak al-Muslimin party, the Muslim faction of the imperial State Duma of four convocations, during the revolutionary events of 1917 and the Civil War is considered.The source base of the study is bills, legislative sources, programs of parties and factions, clerical materials, verbatim records of meetings of the State Duma of all four convocations and Muslim congresses. Methodologically, the article is based on systematization, classification and analysis of these documents. To compare the facts and events related to the activities of the leaders of the Muslim movement of the Russian Empire at the beginning of the twentieth century and to determine their role in the history of interaction between the Muslims of the Volga-Ural region and the Caucasus, the comparative-historical method adopted in domestic science was applied. The conclusions are made that, firstly, the economic and intellectual elite of the Tatar and Azerbaijani peoples stood at the head of the social movement of Muslims of the Russian Empire. Secondly, the main issues facing the Muslim politicians of Russia at the beginning of the twentieth century were questions about the form of government and the autonomy of Muslims and land. Thirdly, the political cooperation between the leaders of the Muslims of the Volga-Ural region and the Caucasus at the beginning of the twentieth century led to the creation of the All-Russian Muslim party "Ittifak al-Muslimin", the Muslim faction of the State Duma, and the convocation of All-Russian Muslim congresses.
Keywords: Muslims; Volga-Ural region; Caucasus; national question; the agrarian question; state structure; social and political movement; revolution.